Modeling of processes of spontaneous ignition using Rothe’s and two-sided approximation methods - Kalinichenko, A.; Sidorov, M. (My University, 2023)
This work is devoted to the Rothe’s method in combination with the twosided approximation method for the spontaneous ignition processes modeling. Mathematical model of self-ignition processes presented as an 2D initialboundary value problem for a semilinear heat conduction equation. The power of the internal heat source is approximated by exponential dependence, based on the Arrhenius equation.
Keywords: Green's function; Hammerstein equation; Rothe's method; self-ignition processes; spontaneous ignition processes; two-dimensional semilinear heat conduction equation; two-sided approximation method